2023
DOI: 10.1001/jamaophthalmol.2023.1821
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parafoveal Diabetic Macular Ischemia on Optical Coherence Tomography Angiography Images to Predict Diabetic Retinal Disease Progression and Visual Acuity Deterioration

Abstract: ImportanceThe presence of diabetic macular ischemia (DMI) on optical coherence tomography angiography (OCTA) images predicts diabetic retinal disease progression and visual acuity (VA) deterioration, suggesting an OCTA-based DMI evaluation can further enhance diabetic retinopathy (DR) management.ObjectiveTo investigate whether an automated binary DMI algorithm using OCTA images provides prognostic value on DR progression, diabetic macular edema (DME) development, and VA deterioration in a cohort of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…In our study, retinal vascular geometry and the fovea were important image patterns for future occurrence of DR based on the DeepDR Plus system, which was consistent with state-of-the-art studies and our previous studies 29 31 , 37 , 38 . Regions of DR-related capillary dropout have been related to local underlying photoreceptor loss, and the fovea may provide information on visual function and foveal perfusion 39 , 40 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, retinal vascular geometry and the fovea were important image patterns for future occurrence of DR based on the DeepDR Plus system, which was consistent with state-of-the-art studies and our previous studies 29 31 , 37 , 38 . Regions of DR-related capillary dropout have been related to local underlying photoreceptor loss, and the fovea may provide information on visual function and foveal perfusion 39 , 40 .…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that vessel density, fractal dimension and foveal avascular zone area could predict DR progression 29 , 30 . Previous studies also support that retinal vascular changes and related variables are associated with DR-related risk factors 31 .…”
Section: Resultsmentioning
confidence: 99%
“…[35,[86][87][88][89] Many researchers have integrated diverse data sources, including fundus images, clinical data, genomic information, and extensive long-term monitoring data, to build predictive models for forecasting the occurrence, progression, and treatment response of DME. [90][91][92][93][94][95] Personalized treatment plans based on deep learning have also attracted considerable attention. Analyzing large-scale clinical data and establishing models to provide customized, individualized treatment plans for each patient can improve treatment outcomes.…”
Section: Emerging Research Areasmentioning
confidence: 99%